2021
DOI: 10.1136/annrheumdis-2021-eular.1363
|View full text |Cite
|
Sign up to set email alerts
|

Ab0573 dupilumab-Induced Enthesitis/Arthritis in Patients With Atopic Dermatitis: A Retrospective Observational Study

Abstract: Background:Atopic dermatitis (AD) is a common skin condition with a prevalence of 2–10% in adults1. IL-4 and IL-13 play a key role in the pathogenesis. Dupilumab, a human IgG4 monoclonal antibody binding the alpha subunit of the IL-4 receptor, blocking IL-4 and IL-13 signaling, has important efficacy in this difficult to treat disease. We first reported a musculoskeletal (MSK) adverse effect of enthesis/arthritis developing in 3 patients in 20192.Objectives:To report the ongoing experience at our centre of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Its frequency in patients starting dupilumab for atopic dermatitis is unknown, but in the single retrospective observational study reported, almost 5% of patients treated with dupilumab for atopic dermatitis were at least minimally affected by inflammatory arthritis. 3 , 4 However, based on the small number of case reports in the literature and our own clinical experience, we suspect that either the frequency reported by Nathan et al 3 was spuriously elevated or that the vast majority of cases are mild enough that they go unrecognized and do not require specific therapy or discontinuation of dupilumab. Cessation of dupilumab appears to reliably resolve the arthritis, 3 , 5 although severe cases may take 6 months to a year after discontinuation to resolve.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Its frequency in patients starting dupilumab for atopic dermatitis is unknown, but in the single retrospective observational study reported, almost 5% of patients treated with dupilumab for atopic dermatitis were at least minimally affected by inflammatory arthritis. 3 , 4 However, based on the small number of case reports in the literature and our own clinical experience, we suspect that either the frequency reported by Nathan et al 3 was spuriously elevated or that the vast majority of cases are mild enough that they go unrecognized and do not require specific therapy or discontinuation of dupilumab. Cessation of dupilumab appears to reliably resolve the arthritis, 3 , 5 although severe cases may take 6 months to a year after discontinuation to resolve.…”
Section: Discussionmentioning
confidence: 88%
“… 3 , 4 However, based on the small number of case reports in the literature and our own clinical experience, we suspect that either the frequency reported by Nathan et al 3 was spuriously elevated or that the vast majority of cases are mild enough that they go unrecognized and do not require specific therapy or discontinuation of dupilumab. Cessation of dupilumab appears to reliably resolve the arthritis, 3 , 5 although severe cases may take 6 months to a year after discontinuation to resolve.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations